Group-based care: does it change problem behaviour? - van Weel, Chris (1980)
As a result of disappointing experiences in managing problem behaviour presented by patients in general practice, a system of team or group-based care was developed at the Ommoord Health Centre in Rotterdam, the Netherlands. However, despite all the care given by social workers, general practitioners, physiotherapists and other members of the primary health care team, the problem behaviour of about half the patients was unaltered. This report concerns the aims and methods of our group meetings and the conditions such as empathy, sincerity and non-possessive warmth which we regard as essential in dealing with problem behaviour. The conditions necessary for improvement, such as independence and responsiveness by patients, are also considered. During our group meetings the team deals with the emotions which patients are experiencing at the time, and patients are encouraged to discover as much as possible about their own possibilities for both influencing and making choices in their lives. Some examples of this type of care are given. Patients react positively to the group-based care approach and some reduction in the consultation rate and in the prescribing of tranquillizers by general practitioners has been shown.